The development of tourism as a young school subject : a comparative curriculum study - Petersen, Joy (School of Education, 2015)
This dissertation is a comparative analysis of three different curricula with the aim of tracking key elements in the development of the South African tourism curriculum. Using Bernstein's theory of the reproduction of pedagogical discourse, the study elucidates the what and how of the intended and assessed tourism curriculum. Within a sociological framework, it employs specifically developed analytical tools to examine different facets of the curriculum. Throughout, the complex and dynamic nature of curriculum development is highlighted. The conclusion illuminates the difficulty of curriculum design of a young subject that has been developed from a fragmented canon and attempts a description of where the South African tourism curriculum finds itself at present.